A Case Report of Local Recurrence Developing 24 Years After Mastectomy for Breast Cancer Recurrence From Breast Cancer After 24 Years. Issue 22 (May 2016) - Xiao, Linlin; Hu, Xudong; Wang, Suzhen; Yong-Sheng, Gao; Yu, Qingxi; Gao, Song; Zhang, Hui; Wei, Yuchun; Zhao, Qian; Yuan, Shuang-Hu
Abstract : Abstract: Introduction: Breast cancer is a commonly diagnosed cancer, in which most patients' metastases (about 75%) occurred in 5 years after the initial diagnosis, especially in 3 years. Recrudescence exceeding 20 years is rarely reported in the past several decades. Case information: A 68-year-old female patient presented with breast cancer in which 3 focal increased 18F-fluorodeoxyglucose uptake in the right supraclavicular lymph node, the mediastinum and sternum were found on positron emission tomography and computed tomography. Then we learned that the patient had suffered from breast cancer and been given a right-sided mastectomy 24 years ago. Histopathology from the mediastinum revealed metastatic, moderately differentiated breast adenomatous cell carcinoma. Conclusion: We report this late recurrence of breast cancer 24 years following mastectomy, suggesting that possible recurrence of this disease with a 24-year latency period should be taken into consideration.